2016
DOI: 10.1039/c6ra14557d
|View full text |Cite
|
Sign up to set email alerts
|

Brönsted acid-mediated annulations of 1-cyanocyclopropane-1-carboxylates with arylhydrazines: efficient strategy for the synthesis of 1,3,5-trisubstituted pyrazoles

Abstract: A diversity-oriented synthesis of 1H-pyrazole derivatives via Brönsted acid-promoted annulations of 1-cyanocyclopropane-1-carboxylates with arylhydrazines has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Synthesis and study of the cyclopropane ring, which is widely present as a key structural motif in many natural and pharmaceutically active compounds, is a challenging task due to its stereoelectronic factors and intrinsic ring strain. Over the past two decades, the domain of donor–acceptor cyclopropanes (D–A cyclopropanes) has experienced an exponential growth since the seminal work by Wenkert, Danishefsky, and Reissig . Chemist’s interest in D–A cyclopropanes has increased, as they are predisposed to provide ready access to multifunctionalized intermediates and key building blocks, for the synthesis of natural products and biologically active molecules through various ring-opening strategies. The ring opening has been largely realized through activation by Lewis-acid , and transition-metal catalysis in both achiral and chiral versions. In addition, D–A cyclopropanes are transformed into various cyclic compounds by Brønsted-acid- and base- induced nucleophilic addition, ring expansion, and cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and study of the cyclopropane ring, which is widely present as a key structural motif in many natural and pharmaceutically active compounds, is a challenging task due to its stereoelectronic factors and intrinsic ring strain. Over the past two decades, the domain of donor–acceptor cyclopropanes (D–A cyclopropanes) has experienced an exponential growth since the seminal work by Wenkert, Danishefsky, and Reissig . Chemist’s interest in D–A cyclopropanes has increased, as they are predisposed to provide ready access to multifunctionalized intermediates and key building blocks, for the synthesis of natural products and biologically active molecules through various ring-opening strategies. The ring opening has been largely realized through activation by Lewis-acid , and transition-metal catalysis in both achiral and chiral versions. In addition, D–A cyclopropanes are transformed into various cyclic compounds by Brønsted-acid- and base- induced nucleophilic addition, ring expansion, and cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemist’s interest in D–A cyclopropanes has increased, as they are predisposed to provide ready access to multifunctionalized intermediates and key building blocks, for the synthesis of natural products and biologically active molecules through various ring-opening strategies. The ring opening has been largely realized through activation by Lewis-acid , and transition-metal catalysis in both achiral and chiral versions. In addition, D–A cyclopropanes are transformed into various cyclic compounds by Brønsted-acid- and base- induced nucleophilic addition, ring expansion, and cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…9 We also successfully used other aroyl-substituted D−A cyclopropane 2-aroyl-3-aryl-1-cyanocyclopropane-1-carboxylates as a substrate for the cycloaddition with arylhydrazines to synthesize 1,3,5-trisubstituted pyrazoles in the presence of a Bronsted acid; however, the cyanoacetate unit was not retained due to the requirement of aromatization. 10 benzoyl-1,1-cyclopropanedicarbonitriles reacted with hydrazine to generate 5-aryl-3-phenylpyrazole derivatives without a malononitrile unit (Scheme 1). 11 Recently, to explore further the preparation of diverse pyrazole derivatives from 2-aryl D− A cyclopropanes and hydrazine or arylhydrazines, we used acetic acid as a catalyst to promote the cyclization of 2-aroyl-3aryl-1,1-dicyanocyclopropanes with arylhydrazines, which provided an efficient approach for the synthesis of fully substituted pyrazolines with a dicyanomethyl group.…”
mentioning
confidence: 99%
“…15 In 2016, we successfully carried out Bronsted acid-promoted (3 + 2)-cycloaddition of 1-cyanocyclopropane 1-esters with arylhydrazines, leading to the production of 1,3,5-trisubstituted pyrazoles in moderate to good yields via removal of cyanoacetate (Scheme 1). 16 Soon afterward, Srinivasan and co-workers reported the nucleophilic ring-opening reactions of trans-2-aroyl-3-aryl-cyclopropane-1,1-dicarboxylates with various arylhydrazines to synthesize 4,5-trans-substituted dihydropyrazoles with a diethyl malonate unit (Scheme 1). 17 Research showed the obviously different reactivities and positions for D−A cyclopropanes with different electronwithdrawing groups.…”
mentioning
confidence: 99%